2021
DOI: 10.1002/cam4.4161
|View full text |Cite
|
Sign up to set email alerts
|

Integrated pan‐cancer of AURKA expression and drug sensitivity analysis reveals increased expression of AURKA is responsible for drug resistance

Abstract: This is an open access article under the terms of the Creat ive Commo ns Attri bution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 77 publications
0
19
0
Order By: Relevance
“…String interaction results indicated interplay of signaling molecules of AURKA pathway in SiHa/RR. AURKA was found to be strongly interacted with p53, Gadd45a, Akt and PCNA and NFκB [23][24][25]. Hyper-proliferative potential of SiHa/RR aided in increased migration and invasion capabilities as found from the result of wound healing assay where SiHa/RR lled the gap at a much faster rate compared to SiHa.…”
Section: Discussionmentioning
confidence: 86%
“…String interaction results indicated interplay of signaling molecules of AURKA pathway in SiHa/RR. AURKA was found to be strongly interacted with p53, Gadd45a, Akt and PCNA and NFκB [23][24][25]. Hyper-proliferative potential of SiHa/RR aided in increased migration and invasion capabilities as found from the result of wound healing assay where SiHa/RR lled the gap at a much faster rate compared to SiHa.…”
Section: Discussionmentioning
confidence: 86%
“…Sperm-associated antigen 5 ( SPAG5 , also known as asstrin) is involved in mitotic spindle formation and chromosome segregation, and has carcinogenic effects in tumorigenesis of various cancer types ( Huang & Li, 2020 ). AURKA is a serine/threonine kinase that is critical for the control of mitotic progression, centrosomal maturation/separation, and mitotic spindle function ( Miralaei et al, 2021 ). Studies have found that AURKA mRNA expression is an independent predictor of poor prognosis in patients with NSCLC ( Al-Khafaji et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“… Confirmed to have Burkholderia pseudomallei infection according to colony cultures 6 using body fluid specimens (blood, pleural fluid, sputum, pus, urine, secretions, etc. ); Administered with antibiotics and necessary treatment by Haikou Hospital of Xiangya School of Medicine, Central South University following the susceptibility test; …”
Section: Methodsmentioning
confidence: 99%
“…Confirmed to have Burkholderia pseudomallei infection according to colony cultures 6 using body fluid specimens (blood, pleural fluid, sputum, pus, urine, secretions, etc. );…”
Section: Methodsmentioning
confidence: 99%